Aplikasi Pengamanan Data Karyawan menggunakan Algoritma Advanced Encryption Standard dan Cloud Computing berbasis Mobile - Adi Kannatasik; Moh. Ali Romli (Jurnal Pendidikan Informatika (EDUMATIC), 2023)
Documents are valuable assets that often contain important information, including employee personal data, and are vulnerable to security threats such as theft and alteration by unauthorized parties. This research aims to develop an Android-based document security application that combines the Advanced Encryption Standard (AES) algorithm and cloud computing technology. This type of research is developed using the System Development Life Cycle (SDLC) model, which involves requirements analysis, design, coding, and testing. At the needs analysis stage, focus is given to employee data that needs to be secured. System design includes data structure, system structure, and user interface (UI). System design includes use case elements, class diagrams, and application architecture. Coding was done using Flutter as the user interface, Laravel as the backend, and MySQL as the database. System testing uses black box testing. Our test results show that the data security application is successful in carrying out the data encryption and decryption processes. Compared to previous web and desktop-based developments, this application provides a more adaptive solution to high mobility in the work environment. Cloud computing integration provides flexibility in data access, and the use of the Android platform significantly increases user mobility.